Acute Effects of High-Level PM2.5 Exposure on Central Blood Pressure. Issue 6 (December 2019) - Fan, Fangfang; Wang, Shixuan; Zhang, Yi; Xu, Dandan; Jia, Jia; Li, Jianping; Li, Tiantian; Zhang, Yan; Huo, Yong
Abstract : Central aortic blood pressure (BP) has been increasingly recognized as having a closer relationship with cardiovascular risks than peripheral BP. However, the effects of particulate matter pollution on central aortic BP have not been clearly demonstrated. In this study, we assessed the association between short-term ambient fine particulate matter (with an aerodynamic diameter ⩽2.5 μm; PM2.5 ) exposure and central aortic BP in a Chinese community-based population. A total of 4715 visits were in our final analysis, including 2151 visits at the baseline and 2564 visits at the follow-up. Central aortic systolic BP (cSBP) was measured noninvasively using the method of radial artery tonometry with Omron HEM-9000AI machine. Data from air pollution monitoring stations were used to estimate daily PM2.5 exposure. Generalized additive mixed models with clinical and meteorologic covariates adjusted were used to examine the association between PM2.5 exposure and cSBP. The relationships between PM2.5 exposure and cSBP were nonlinear, and significant increments of cSBP were observed when the PM2.5 exposure concentration was above 100 μg/cm 3 . An interquartile range increase (80.25 μg/m 3 ) in daily PM2.5 on the day of cSBP measurement (lag 0 day) was associated with 2.54 mm Hg (95% CI, 0.92–4.16) elevation in cSBP. The associations of PM2.5 with cSBP were not modified by age, sex, body mass index, medications, and comorbid diseases except for cardiovascular disease. Our findings demonstrated that short-term exposure to high concentration of ambient PM2.5 above 100 μg/cm 3 was associated with significant increases in central aortic BP in a Chinese community-based population. Abstract : Supplemental Digital Content is available in the text.